ANALISIS KONFLIK BATIN TOKOH UTAMA DALAM NOVEL REMBULAN TENGGELAM DI WAJAHMU MENGGUNAKAN PENDEKATAN PSIKOLOGI SEBAGAI ALTERNATIF PEMBELAJARAN SASTRA DI SMA - Iklima Aulia Salsabila; Dheni Harmaen; Adi Rustandi (STKIP Subang, 2023)
The purpose of this study is to describe the intrinsic elements in the novel Rembulan Sinking di TFacemu by Tere Liye. The method used in this study is qualitative descriptive with a structural approach. Data collection techniques used include recording and reading techniques, as well as documentation. The results of the study are, (1) the intrinsic elements contained in Tere Liye's novel The Moon Sinks in Your Face include theme, plot (early stage, middle stage, and final stage, setting (place, time, and atmosphere), characters and characterizations, point of view (third person), and language style (sarcasm, hyperbole, personification, metaphor, simile, parallelism, allegory, metonymy, and repetition), (2) the conflicts of characters contained in the novel Rembulan Sinking di TFacemu by Tere Liye include inner conflicts and physical conflicts, as well as internal conflicts and external conflicts.